Riding the tide: assessing South Korea's hedging strategy through regional security initiatives. Issue 3 (4th May 2023) - Lee, Yaechan
Abstract: This article examines how South Korea has used the ASEAN Plus security platforms to hedge between the US and China and why it has not participated in the FOIP strategy. It argues that the platforms' neutral guise, owing to ASEAN centrality and their global norms-based agenda has allowed Korea to passively voice its alignment with the US, thereby answering to the pressure for a higher commitment from the US and clearing the political risk of linking the alignment decision to its own views. It asserts, therefore, that access to effective multilateral security platforms allows higher leverage to the weaker ally in an asymmetric alliance relationship.